Analisis Kualitas Layanan Pada Akun Instagram Sebagai Media Informasi Bagi Siswa/i dengan Metode E Servqual - Septia G, Andi; Mustuka U, Ersa; Divara A, Audry; Borroek, Maria Rosario (TIN: Terapan Informatika Nusantara, 2024)
The development of information technology in Indonesia is increasing rapidly from day to day. One of the effects of the development of information technology is that it can absorb more positive things, users can adapt and get the information needed by society. Instagram is a photography-based social networking service. Instagram allows users to take photos, videos and add filters to add an interesting impression to the photos. Primarily, Instagram is more focused on smartphone devices such as Android and iOS. The research aims to analyze the quality of service on the YADIKA Vocational School Jambi City Inatagram account as an information medium from the e-servqual variable. Using the e-servqual method, the variables used are Compesation, Contact, Efficiency, Fullfillment, Privacy, Responsiveness, System Availability. The data collection technique used is by distributing questionnaires or questionnaires. The data statistical methods used are descriptive statistics and Partial Least Square (PLS) with the SmartPLS version 3.0 program. The results of this researcher are from 7 E-Servqual variables, 4 which significantly influence the Service Quality on the Instagram account of SMK YADIKA JAMBI CITY, namely Efficiency, Privacy, Compensation, Contact and 3 variables which do not influence the Service Quality of the Instagram account of SMK YADIKA JAMBI CITY, namely Fullfillment, System Availability, Responsiveness.